Involvement of Mammalian RF-Amide Peptides and Their Receptors in the Modulation of Nociception in Rodents - Ayachi, Safia; Simonin, Frédéric (Frontiers in Endocrinology, 2014)
Mammalian RF-amide peptides, which all share a conserved carboxyl-terminal Arg-Phe-NH2 sequence, constitute a family of five groups of neuropeptides that are encoded by five different genes. They act through five G protein-coupled receptors and each group of peptide binds to and activates mostly one receptor: RF-amide related peptide (RFRP) group binds to NPFFR1, neuropeptide FF (NPFF) group to NPFFR2, pyroglutamylated RF-amide peptide (QRFP) group to QRFPR, prolactin releasing peptide (PrRP) group to PrRPR, and kisspeptin group to Kiss1R. These peptides and their receptors have been involved in the modulation of several functions including reproduction, feeding and cardiovascular regulation. Data from the literature now provide emerging evidence that all RF-amide peptides and their receptors are also involved in the modulation of nociception. This review will present the current knowledge on the involvement in rodents of the different mammalian RF-amide peptides and their receptors in the modulation of nociception in basal and chronic pain conditions as well as their modulatory effects on the analgesic effects of opiates.